Mentoring Top Leadership Promotes Organizational Innovativeness through Psychological Safety and Is Moderated by Cognitive Adaptability - Moore, James H.; Wang, Zhongming (Frontiers in Psychology, 2017)
Mentoring continues to build momentum among startups and established enterprises due to its positive impact on individuals and organizations. Unlike previous studies, this research focuses on mentoring higher level leadership, such as the CEO, and demonstrates its unique relationship to organizational innovativeness. Our sample included 200 mentored executives and entrepreneurs who personally identify and exploit opportunities. Our findings confirm that mentoring top leaders positively relates to their perceived innovativeness of the organization and that the relationship is mediated by these leaders’ perception of psychological safety within the organization. Our findings also confirm that the relationship is negatively moderated by these leaders’ cognitive adaptability. The reliability and validity of the results have been proved by using confirmatory factor analysis and advanced regression analytics. As a result, this work demonstrates the value of mentoring top leadership and advocates the importance of establishing a psychologically safe environment to inspire not only top leadership to try new avenues but also for all those within the organization to speak up and speak out. Additionally, our findings encourage organizations to proactively and selectively prioritize mentoring among top leadership, taking into account their differing levels of cognitive adaptability. Finally, further research could focus on how to provide greater support for mentors of higher level leaders.